Disorganization/Cognitive and Negative Symptom Dimensions in the At-Risk Mental State Predict Subsequent Transition to Psychosis - Demjaha, Arsime (Oxford University Press, 2012)
OBJECTIVE: The at-risk mental state (ARMS) is associated with a very high risk of psychosis, but it is difficult to predict which individuals will later develop psychosis on the basis of their presenting symptoms. We investigated psychopathological dimensions in subjects with an ARMS and examined whether particular symptom dimensions predicted subsequent transition to psychosis. METHOD: The sample comprised 122 subjects (aged 16–35 years) meeting Personal Assessment and Crisis Evaluation clinic criteria for the ARMS recruited through Outreach and Support in South London, a clinical service for people with an ARMS. A principal axis factor analysis was performed on symptom scores, obtained at presentation from the Comprehensive Assessment of the At-Risk Mental State, using Varimax rotation. The relationship between dimension scores and transition to psychosis during the following 24 months was then examined employing Cox regression analysis. RESULTS: Factor analysis gave rise to a 5-factor solution of negative, anxiety, disorganization/cognitive, self-harm, and manic symptom dimensions, accounting for 37% of the total variance. Scores on the negative and on the disorganization/cognitive dimensions were associated with transition to psychosis during the follow-up period (P = 0.044 and P = 0.005, respectively). CONCLUSION: The symptoms of the ARMS have a dimensional structure similar to that evident in patients with schizophrenia except for the positive symptom dimension. The association between scores on the disorganization/cognitive and negative dimensions and later transition is consistent with independent evidence that formal thought disorder, subjective cognitive impairments, and negative symptoms are linked to the subsequent onset of psychosis.